Notary's Responsibility For Authentic Deeds Which The Participant Uses A Fake Identity In Sukoharjo Regency - Yulia Ardana, Shindi; Sudarwanto, Sentot; Elok Puri maharani, Andina (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Authentic deeds have a very important position. This is because authentic deeds are recognized by law and have very strong evidentiary power. Often cases of identity forgery by the witness used in the making of authentic deeds are found, which have a serious impact and cause various problems. The notary is only in charge of recording the data and information provided by the witness, as is known, the notary does not have the authority to conduct a material and passive investigation of false information and identities by the witnesses, but often if the notary is dragged and held accountable in the event of a dispute. The purpose of this writing, in general, the author wants to develop legal knowledge in the field of notary law. The writing in this journal analyzes the responsibility of notaries for authentic deeds that use false identities and the efforts that can be made by notaries to prevent identity forgery in making authentic deeds. So that unwanted things do not happen to people in good faith and notaries. The method of approach used is a qualitative approach, a research method that focuses on a deep understanding of the phenomenon being studied through the interpretation of context and meaning. This approach tends to generate descriptive data in the form of words, imagery, or narratives, and focuses more on understanding how and why a phenomenon occurs rather than simply measuring its frequency or magnitude. The results of the study show that the responsibility of a notary in making authentic deeds can be seen from the negligence of the Notary in making authentic deeds, the negligence in question is if the notary has made a deed that is not in accordance with the existing rules or the notary consciously and deliberately makes a deed with the aim of benefiting himself or certain parties, then the notary can be held responsible, However, if the negligence that arises is not from the notary but from the witness, either intentionally or unrelated to the identity or false information provided by the witness which is used as the basis for making an authentic deed and makes the deed incorrect, then it becomes the responsibility of the parties themselves as it is known that the notary has no obligation and is passive in terms of materially investigating the information and or the identity submitted by the witness.